Muco-bioadhesive containing Ginger officinale extract in the management of recurrent aphthous stomatitis a double blind clinical study - Parya Haghpanah; Aliakbar Moghadamnia; Amin Zarghami; Mina Motallebnejad (Babol University of Medical Sciences, 2015)
Background and objectives: Recurrent aphthous stomatitis (RAS) is the most common oral mucosal lesions in the general population. Various treatment modalities have been used but no specific therapy proved to be definitive. Ginger Officinale (ginger) indicated to have anti-inﬂammatory properties in herbal medicine. Thus, this study aimed to evaluate the efficacy of Gingerginger containing bioadhesive in treatment of aphthous ulcers. Material and Methods: This was a double-blinded placebo randomized controlled trial. Fifteen patients enrolled in this study. The clinical efficacy of the mucoadhessive on pain, inflammatory zone and ulcer's diameter in the test period was compared with that of the base treatment and no treatment periodss during 10 days of study. Results: Significant reduction in pain as observed on day 5 between placebo (using base bioadhesives) and no-treatment periods at the first phase of the study (4.53 vs. 3.27 p=0.038.( Reduction in inflamed halo diameters was significant on day 1 between no-treatment and ginger containing bioadhesives )46.73 vs 28.67 p=0.044). Other variables such as ulcer's diameter did not indicate any significant differences in both periods. Conclusion: This study indicated that ginger bioadhesive is capable to relieving pain of RAS. However, its efficacy on ulcer diameter, inflamed halo and healing time was not significantly different compared to the results of the placeb received period.